"Carnival", 1938, Trinidad - (:unkn) unknown (My University, 2009)
Masqueraders parade the streets during the Carnival celebrations in Trinidad.
Colour: Black and White: Style: Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Carnival--Trinidad and Tobago; Carnival costume--Trinidad and Tobago; Architecture--Trinidad and Tobago; 1938